SEMANTIC APPROACH (BAYANI) IN ISLAMIC STUDIES - Wahdini, Muhammad (State Islamic University of Datokarama Palu, 2021)
The Semantic Approach (Bayani) is an approach in the study of Islamic studies to comprehend Islam comprehensively. This research refers to some literature related to the semantic approach. Semantics as an epistemological system includes three pairs of basic concepts, namely pronunciation-meaning, asl-far, and substance-accidents. The first and second concepts include methodological aspects, while the third concept includes aspects of the world view. The urgency of this method is that this approach is used to extract the meaning of zahir from lafadz and 'ibarah who is zahir and take the istinbath of the laws of al nushush' an diniyyah and the Qur'an in particular. So this approach is classified as a textual method.